2010
DOI: 10.1155/2010/402593
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Zonula Occludens (ZO) Proteins

Abstract: ZO (zonula occludens) proteins are scaffolding proteins providing the structural basis for the assembly of multiprotein complexes at the cytoplasmic surface of intercellular junctions. In addition, they provide a link between the integral membrane proteins and the filamentous cytoskeleton. ZO proteins belong to the large family of membrane-associated guanylate kinase (MAGUK)-like proteins comprising a number of subfamilies based on domain content and sequence similarity. Besides their structural function at ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 106 publications
6
148
2
4
Order By: Relevance
“…Significantly, CDH1 and TJP1 proteins had a more punctate distribution. In the case of TJP1, the protein was often localized in the nucleus, suggesting that inhibition of GRHL function interferes with the shuttling of TJP1 between the nucleus and cell membrane (21).…”
Section: Grhl2 Regulates the Expression Of Multiple Genes In Undiffermentioning
confidence: 99%
“…Significantly, CDH1 and TJP1 proteins had a more punctate distribution. In the case of TJP1, the protein was often localized in the nucleus, suggesting that inhibition of GRHL function interferes with the shuttling of TJP1 between the nucleus and cell membrane (21).…”
Section: Grhl2 Regulates the Expression Of Multiple Genes In Undiffermentioning
confidence: 99%
“…ZO-1 is one of three zonula occludens proteins belonging to a family of multi-domain proteins known as the membrane-associated guanylate kinase homologs (MAGUKs) (Fanning et al 1998). Previous studies have shown MAGUKs are not only essential structural proteins at the site of tight and gap junctions but also function in signal transduction pathways related to gene expression and cell behavior (Bauer et al 2010). ZO-1 is found in acinar and ductal cells of salivary epithelium (Maria et al 2008) and is critical for claudin polymerization (Umeda We were able to demonstrate that ZO-1 protein expression levels are unaltered in NOD/ShiLtJ mice as compared with control mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most well-known tight junction proteins are the Zonula Occludens (ZO) proteins, which act as scaffolding in the plasma membrane and provide a cytoplasmic structural anchor for the paracellular protein complexes [3]. Tight junctions also serve as a primary barrier or channel through which solutes and ions are selectively transported through the intercellular space.…”
Section: Introductionmentioning
confidence: 99%